The dawn of non-human primate models for neurodevelopmental disorders. (December 2020) - Aida, Tomomi; Feng, Guoping
Highlights: Genome editing technologies have made it feasible to generate genetically modified NHP models. Genetic NHP models have certain advantages to study higher brain function and dysfunction in neurodevelopmental disorders. Challenges for pushing genetic NHP models forward identified. Opportunities for next generation genetic NHP models proposed. Abstract : Non-human primates (NHPs) have been proposed as good models for neurodevelopmental disorders due to close similarities to humans in terms of brain structure and cognitive function. The recent development of genome editing technologies has opened new avenues to generate and investigate genetically modified NHPs as models for human disorders. Here, we review the early successes of genetic NHP models for neurodevelopmental disorders and further discuss the technological challenges and opportunities to create next generation NHP models with more sophisticated genetic manipulation and faithful representations of the human genetic mutations. Taken together, the field is now poised to usher in a new era of research using genetically modified NHP models to empower a more rapid translation of basic research and maximize the preclinical potential for biomarker discovery and therapeutic development.